"Double carbapenem" and oral fosfomycin for the treatment of complicated urinary tract infections caused by blaNDM‐harboring Enterobacteriaceae in kidney transplantation. Issue 1 (27th November 2017) - Rosa, Rossana; Rudin, Susan D.; Rojas, Laura J.; Hujer, Andrea M.; Perez‐Cardona, Armando; Perez, Federico; Bonomo, Robert A.; Martinez, Octavio; Abbo, Lilian M.; Camargo, Jose F.
Abstract: Infections with carbapenemase‐producing carbapenem‐resistant Enterobacteriaceae represent an emergent problem worldwide. Treatment of infections caused by New Delhi metallo‐beta‐lactamase (NDM)‐harboring Enterobacteriaceae is particularly challenging as it frequently involves the use of nephrotoxic agents, which is problematic in kidney transplant recipients and non‐renal transplant patients with marginal kidney function. We present two cases of urinary tract infections caused by NDM‐harboring Enterobacteriaceae successfully treated with a combination of "double carbapenem" and oral fosfomycin.